2022
DOI: 10.1056/nejmoa2206606
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Revascularization for Ischemic Left Ventricular Dysfunction

Abstract: BACKGROUNDWhether revascularization by percutaneous coronary intervention (PCI) can improve event-free survival and left ventricular function in patients with severe ischemic left ventricular systolic dysfunction, as compared with optimal medical therapy (i.e., individually adjusted pharmacologic and device therapy for heart failure) alone, is unknown. METHODSWe randomly assigned patients with a left ventricular ejection fraction of 35% or less, extensive coronary artery disease amenable to PCI, and demonstrab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
166
2
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(235 citation statements)
references
References 21 publications
2
166
2
5
Order By: Relevance
“…25 However, the REVIVED-BCIS2 trial (Revascularisation for Ischaemic Ventricular Dysfunction-British Cardiovascular Intervention Society 2) failed to show any clinical benefit of PCI over medical treatment in such patients. 26 In this study, there was no between-group difference in cardiac events in patients with ejection fraction ≤40%. However, this was a subgroup analysis with limited sample size.…”
Section: Discussionmentioning
confidence: 49%
“…25 However, the REVIVED-BCIS2 trial (Revascularisation for Ischaemic Ventricular Dysfunction-British Cardiovascular Intervention Society 2) failed to show any clinical benefit of PCI over medical treatment in such patients. 26 In this study, there was no between-group difference in cardiac events in patients with ejection fraction ≤40%. However, this was a subgroup analysis with limited sample size.…”
Section: Discussionmentioning
confidence: 49%
“…Although randomized data on the direct comparison between CABG and PCI in HFrEF is lacking, a retrospective study covering 12,113 patients performed in Ontario demonstrated that patients undergoing PCI had a significantly higher mortality (OR 1.6 95%CI: 1.3–1.7) and rate of major adverse cardiovascular events than patients treated with surgical revascularization [ 90 ]. In the recent REVIVED-BCIS2 trial, PCI in patients with LVEF ≤ 35% failed to show any benefit in terms of a reduction in mortality or rate of hospitalizations for HF in comparison to pharmacotherapy, neither did it translate into an improved LVEF [ 91 ]. It should be noted, however, that a considerable proportion of patients with HFrEF and a high operative risk may benefit from PCI if feasible [ 92 ].…”
Section: Functional Mitral Valve Insufficiency: a Common Pitfall In T...mentioning
confidence: 99%
“… HF Aetiology Specific Aetiology Specific Treatment on Top of GDMT/CRT/Treatment of fMR Probability of HFimpEF Clinical Features Refs. Ischaemic MI-related myocardial scar with further remodelling Myocardial revascularization in patients with viable myocardium Preference for CABG vs. PCI in patients with HFrEF Low The most frequent aetiology of HFrEF Ischaemic aetiology is generally associated with a worse prognosis than non-ischaemic aetiology CABG in HFrEF is related with survival benefit and a lower risk of recurrent myocardial infarction and revascularization than PCI CABG and PCI may promote reverse remodelling with a significant increase in LVEF Viability testing prior to revascularization predicts HFimpEF but does not predict clinical outcome [ 88 , 89 , 90 ] Global ischemia/myocardial stunning/freezing High Dilated cardiomyopathy Familial/sporadic DCM In selected cases of inflammatory viral-negative myocarditis, immunosuppressive treatment may be beneficial RCT are ongoing Moderate-to-high Dilatation of LV and systolic dysfunction without significant lesions in coronary arteries and a lack of overt secondary causes of HFrEF Variable outcome and chance of HFimpEF depending on genetic variants: tTTN genes mutations predict a good response to pharmacological treatment Active viral myocarditis steroid/immunosuppressive treatment is contraindicated except for Loeffler and Giant Cell myocarditis Inflammatory, viral-negative DCM immunosuppressive treatment may be beneficial [ 91 , 93 , 96 , 97 , 98 , …”
Section: Functional Mitral Valve Insufficiency: a Common Pitfall In T...mentioning
confidence: 99%
“…The STICH (Surgical Treatment for Ischemic Heart Failure) trial proved that CABG is superior to medical therapy in patients with ischemic cardiomyopathy at a ten-year follow-up [ 53 ]. On the other hand, the most recent REVIVED trial has questioned the reasonableness of PCI in patients with severe ischaemic LV dysfunction [ 54 ]. Importantly, the study included 95 patients with LMCAD.…”
Section: Evidence Supporting Lmca Revascularizationmentioning
confidence: 99%